Learning organisation and sundanese leadership as drivers of teachers’ innovative behaviour: the mediating role of psychological empowerment - Tanti Ardianti; Didik Notosudjono; Hendarman Hendarman (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
Teachers’ innovative behaviour is critical for maintaining educational quality and organisational adaptability. Despite its importance, the psychological mechanisms by which organisational and culturally grounded leadership contexts promote such behaviour, especially in non-Western settings, remain underexplored. Guided by empowerment theory, this study proposes and empirically tests a process-oriented model in which a learning organisation and Sundanese leadership shape teachers’ innovative behaviour through psychological empowerment. A quantitative survey was administered to 178 permanent foundation teachers from private junior high schools in East Bogor Regency, Indonesia. The data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) to assess both direct and indirect relationships among the study constructs. The results show that learning organisation significantly affects psychological empowerment but not teachers’ innovative behaviour. Sundanese leadership also does not directly influence innovative behaviour. Psychological empowerment significantly affects innovative behaviour and fully mediates the effects of learning organisation and Sundanese leadership. This study contributes to the literature by integrating learning organisation, Sundanese leadership, and psychological empowerment within a unified explanatory framework and highlighting the importance of cultural context in understanding teacher innovation. The findings imply that schools should strengthen teachers’ psychological empowerment and culturally grounded leadership practices to effectively foster innovative behaviour among teachers.